Assessment of brainstem reflexes improves the diagnostic sensitivity of multimodal evoked potentials, MRI and clinical testing in the investigation of brainstem function in multiple sclerosis. Issue 3 (March 2016) - Magnano, I.; Pes, G.M.; Ginatempo, F.; Cabboi, M.P.; Pilurzi, G.; Conti, M.; Rothwell, J.C.; Deriu, F.
Abstract : Background: Brainstem (BS) functions are conventionally studied by multimodal evoked potential (EP) recordings, MRI and clinical examination (CLIN). In Multiple Sclerosis (MS), increasing evidence accounts for a BS involvement, often undetected by standard testing. Recently, brainstem reflexes (BSRs) have drawn attention in evaluating BS dysfunction in MS especially the vestibulocollic (VCR) and vestibuloocular reflexes. In contrast, the vestibulomasseteric (VMR), acousticmasseteric (AMR) and trigeminocollic (TCR) reflexes have never been studied systematically in MS. Aims: to investigate whether the diagnostic sensitivity of CLIN, EPs and MRI can be improved adding the assessment of VMR, AMR, TCR and VCR either as single reflexes or in a 4-BSR battery. Methods: The 4-BSR battery was recorded in 60 patients (33.3 ± 8.3 yrs) with relapsing-remitting MS (illness duration 8.2 ± 6.4 yrs). EP set included standard BAEPs, median and tibial SEPs Conventional MRI scans were focused on the BS lesion load. Group differences and correlations between variables were analysed with Mann–Whitney U test and Mc Nemar test. Results: Distribution of BSR and EP abnormality frequencies in MS was: VMR 62.1%, AMR 55.1%, TCR 58.6%, VCR 25.9%; BAEPs 37.3%, median SEPs 60.3% and tibial SEPs 58.6%. Overall, BS dysfunction was detected as follows: BSRs 86.9%, EPs 82.7%, MRI 71.7%, CLIN 37.7%. While the performance of BSRs and EPs, taken separately, was not significantly higher than that of combined MRI/CLIN testing (70%), the paired use of BSRs/EPs had a sensitivity of 93.3%, which was significantly superior ( p  = 0.007), in a subset of patients with a disease duration ⩽6.4 yrs. Conclusions: BSRs revealed brainstem lesions otherwise undetected by CLIN and MRI, thus providing additional evidence of BS dysfunction in MS. Noteworthy, BSRs could effectively complement the usual EP testing in early detection of clinically and radiologically silent lesions. This may encourage EPs/BSRs paired use in newly diagnosed. FISM GRANTS 2008/R/9 and 2011/R/17.